Intracellular Cytokine Flow Cytometry to Differentiate between Active and Latent Tuberculosis through Assessment of Tuberculosis-specific Cytokines - Sindhura Lakshmi Koulmane Laxminarayana; Sushma Belurkar; Kavitha Saravu; Shilna Muttickal Swaminathan (Journal of Applied Hematology)
BACKGROUND: Immune assays, like QuantiFeron-TB Gold (QFT), are available for the diagnosis of latent tuberculosis infection (LTBI). Intracellular cytokine flow cytometry (ICCFC) can be used to assess T-cell immune responses specific to tuberculosis (TB). We studied the role of ICCFC in differentiating active pulmonary TB (Mycobacterium tuberculosis [MTB]) from LTBI in comparison with QFT. METHODS: A prospective study of adult patients with MTB, LTBI, and healthy controls was performed over 1 year. QFT, ICCFC, and lymphocyte subsets were tested. The diagnostic performance of the ICCFC in detecting LTBI and MTB in comparison with the QFT was analyzed. RESULTS: Twenty-six participants were included in the study. The expression of interferon gamma (IFN-γ) and interleukin (IL)-2 by MTB-specific CD4+ T cells, absolute counts, and percentages of CD3+ and CD4+ T-cells was significantly different between the MTB and LTBI groups [P < 0.001]. The frequency of cytokine-expressing CD4+ T-cells correlated well with IFN-γ levels by QFT (IFN-γ, rho 0.736, P < 0.001 and IL-2, rho 0.726, P < 0.001). The frequency of IFN-γ and IL-2 expressing CD4+ T-cells had an area under the curve of 0.946 and 0.943, respectively, compared to QFT in detecting LTBI. CONCLUSION: ICCFC is a valuable tool for detecting LTBI in household contacts with MTB.